2012
DOI: 10.2169/internalmedicine.51.7529
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Ameliorates Impaired the Mitochondrial Function and Prevents Stroke-like Episodes in Patients with MELAS

Abstract: Objective Post-transcriptional taurine modification at the first anticodon ("wobble") nucleotide is deficient in A3243G-mutant mitochondrial (mt) tRNA Leu(UUR) of patients with myopathy, encephalopathy, lactic acidosis, and stroke-like episodes (MELAS). Wobble nucleotide modifications in tRNAs have recently been identified to be important in the accurate and efficient deciphering of codons. We herein examined whether taurine can alleviate mitochondrial dysfunction in patient-derived pathogenic cells and preve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 14 publications
(25 reference statements)
1
37
0
Order By: Relevance
“…The decrease in intracellular: extracellular taurine ratio attenuates the protective role of taurine and could potentiate neuronal damage during ischemia. The administration of exogenous taurine protects the neuropile in ischemic stroke, evident from numerous experimental reports [23,63,65,69,70,73,140,141,142,144,154,155,156,160,176,179,190,206,207,208,209,210,212,217]. Exogenous taurine is able to elicit its neuroprotective mechanisms both at the intracellular and the extracellular level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The decrease in intracellular: extracellular taurine ratio attenuates the protective role of taurine and could potentiate neuronal damage during ischemia. The administration of exogenous taurine protects the neuropile in ischemic stroke, evident from numerous experimental reports [23,63,65,69,70,73,140,141,142,144,154,155,156,160,176,179,190,206,207,208,209,210,212,217]. Exogenous taurine is able to elicit its neuroprotective mechanisms both at the intracellular and the extracellular level.…”
Section: Discussionmentioning
confidence: 99%
“…Rikimaru and colleagues using a culture system of MELAS patient-derived pathogenic cells reported that a high concentration of taurine (40 mM for 4 day exposure) was able to reverse the mitochondrial dysfunction observed in these patients. In their study, taurine increase the oxygen consumption rate, increased the Δψm in a time-dependent and dose-dependent (0 mM, 20 mM and 60 mM) manner and reduced oxidative stress [160]. The study also reported that the MRI of MELAS patients, treated with taurine, showed a reduction in the spread of the ischemic infarct to different brain region.…”
Section: Anti-ischemic Stroke Mechanisms Of Taurinementioning
confidence: 99%
See 2 more Smart Citations
“…Contrarily, lack of this modification leads to errors in translation of proteins encoded by the mitochondrial genome. These include enzymes of the electron transport chain, the defect of which causes superoxide generation and the ensuing oxidative stress (Jong et al, 2012), as well as gives rise to mitochondrial encephalomyopathic diseases in mammals (Rikimaru et al, 2012;Umeda et al, 2005;Yasukawa et al, 2005). Since three of the COX subunits are encoded by the mitochondrial genome, the reductions in hepatic protein content (Fig.…”
Section: Impact On the Liver And General Metabolismmentioning
confidence: 99%